PROTECTIVE COVERINGS FOR ICE AND SNOW. - STEHLE, N. S. (1966)
Summer deterioration of snow and ice surfaces due to high solar radiation and near-melting temperatures hampers the year-round use of natural ice islands and smooth sea-ice areas in the Arctic Ocean, and permanent snow and ice areas in the Antarctic. Sawdust has been used successfully in the California Sierras for protecting compacted-snow areas during periods of alternating above-and below-freezing temperatures and high solar radiation, but its scarcity and shipping bulk preclude its use in polar areas. Urethane foam has proven even more successful than sawdust as a protective covering in laboratory tests during alternating above-and below-freezing temperatures and simulated solar radiation of 0.8 Langley/min (gm-cal sq cm/min). Use of snow or chipped ice on ice surfaces in the Antarctic has generally provided sufficient protection to prevent deterioration and ablation, but warmer environments may preclude use of these natural materials. The use of snow and chipped ice as protective coverings should be exploited and further studies should be made to gain quantitative knowledge on the protective properties of these natural materials and to determine the practical application of urethane foam in polar areas. (Author)